Derecruitment Test and Surfactant Therapy in Patients with Acute Lung Injury - Alexey A. Smetkin; Vsevolod V. Kuzkov; Konstantin M. Gaidukov; Lars J. Bjertnaes; Mikhail Y. Kirov (Critical Care Research and Practice)
Introduction. A recruitment maneuver (RM) may improve gas exchange in acute lung injury (ALI). The aim of our study was to assess the predictive value of a derecruitment test in relation to RM and to evaluate the efficacy of RM combined with surfactant instillation in patients with ALI. Materials and Methods. Thirteen adult mechanically ventilated patients with ALI were enrolled into a prospective pilot study. The patients received protective ventilation and underwent RM followed by a derecruitment test. After a repeat RM, bovine surfactant (surfactant group, n=6) or vehicle only (conventional therapy group, n=7) was instilled endobronchially. We registered respiratory and hemodynamic parameters, including extravascular lung water index (EVLWI). Results. The derecruitment test decreased the oxygenation in 62% of the patients. We found no significant correlation between the responses to the RM and to the derecruitment tests. The baseline EVLWI correlated with changes in SpO2 following the derecruitment test. The surfactant did not affect gas exchange and lung mechanics but increased EVLWI at 24 and 32 hrs. Conclusions. Our study demonstrated no predictive value of the derecruitment test regarding the effects of RM. Surfactant instillation was not superior to conventional therapy and might even promote pulmonary edema in ALI.